Synthesizing agent for Wumpus World / Ainul Azlinda Abu Bakar - Abu Bakar, Ainul Azlinda (2004)
The developing of intelligent agent has become a major research for many researchers currently. However, a little had focused on developing an agent synthesis. The domain of this thesis is traditional wumpus world that is enhanced and modified to be the synthesizing agent wumpus world. Therefore, this thesis objective is'to identify the enhancement and modification needed and to create synthesizing agent algorithm that is sound for the synthesizing agent wumpus world. Agent synthesis is an automatic programming that will automatically deliver an agent into an environment, and will do the task given successfully in that particular environment. The major enhancement and modification have been made to the rules, actuators, and sensors of the traditional wumpus world. This thesis used a few approach in developing agent synthesis such as depth-first search and synthesis scheme. This technique is used by the agent synthesis to ensure that it will be synthesize into a right square and at the right time. As a result, the agents are able to achieve its goal in a shorter time and more accurately. This thesis would give ideas for future work in producing more quality agent syntheses. In conclusion, synthesizing agent could be a great solution to overcome the problem in an environment.